Kolaborasi Membangun Desa Melalui Aksi Nyata Mahasiswa KKN Dalam Melakukan Pendataan Kemiskinan Ekstrim Dan Edukasi Stunting Di Desa Regapu’u - Yoseph Darius Purnama Rangga; Rosalia Yuliani; Febronia Inexia; Elisabeth Conchita Naru; Amelia Ardita Silviana Moy; Maria Ayulina Da Noa; Paulus Mude (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The Community Service Program (KKN) is a form of student dedication to society aimed at supporting sustainable rural development. In Regapu’u Village, KKN students implemented a collaborative program focusing on two strategic issues: extreme poverty data collection and stunting prevention education. The data collection was carried out through door-to-door visits to obtain accurate information regarding the residents' social and economic conditions. The data was then used as a basis for village policy planning and social assistance distribution. Meanwhile, the stunting education was conducted through outreach activities targeting pregnant women, breastfeeding mothers, and families with toddlers, covering topics such as nutrition, parenting practices, and sanitation. The methods used included participatory observation, interviews, educationaloutreach, and demonstrations of nutritious food preparation (mung bean porridge). The results of the program showed an increase in community awareness regarding child nutrition and health, as well as the availability of more accurate poverty data for the village government. This activity demonstrates that collaboration between students, the community, and local authorities can contribute significantly to addressing poverty and preventing stunting at the local level